Sensorimotor plasticity after spinal cord injury: a longitudinal and translational study. Issue 1 (1st December 2018) - Jutzeler, Catherine R.; Streijger, Femke; Aguilar, Juan; Shortt, Katelyn; Manouchehri, Neda; Okon, Elena; Hupp, Markus; Curt, Armin; Kwon, Brian K.; Kramer, John L. K.
Abstract: Objective: The objective was to track and compare the progression of neuroplastic changes in a large animal model and humans with spinal cord injury. Methods: A total of 37 individuals with acute traumatic spinal cord injury were followed over time (1, 3, 6, and 12 months post‐injury) with repeated neurophysiological assessments. Somatosensory and motor evoked potentials were recorded in the upper extremities above the level of injury. In a reverse‐translational approach, similar neurophysiological techniques were examined in a porcine model of thoracic spinal cord injury. Twelve Yucatan mini‐pigs underwent a contusive spinal cord injury at T10 and tracked with somatosensory and motor evoked potentials assessments in the fore‐ and hind limbs pre‐ (baseline, post‐laminectomy) and post‐injury (10 min, 3 h, 12 weeks). Results: In both humans and pigs, the sensory responses in the cranial coordinates of upper extremities/forelimbs progressively increased from immediately post‐injury to later time points. Motor responses in the forelimbs increased immediately after experimental injury in pigs, remaining elevated at 12 weeks. In humans, motor evoked potentials were significantly higher at 1‐month (and remained so at 1 year) compared to normative values. Conclusions: Despite notable differences between experimental models and the human condition, the brain's response to spinal cord injury is remarkably similar between humans and pigs. Our findings further underscore the utility of this large animal model in translational spinal cord injury research.